2022
DOI: 10.3389/feduc.2022.884635
|View full text |Cite
|
Sign up to set email alerts
|

Exploring First Semester Changes in Domain-Specific Critical Thinking

Abstract: Critical thinking is a common aim for higher education students, often described as general competencies to be acquired through entire programs as well as domain-specific skills to be acquired within subjects. The aim of the study was to investigate whether statistics-specific critical thinking changed from the start of the first semester to the start of the second semester of a two-semester statistics course, where the curriculum contains learning objectives and assessment criteria related to critical thinkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
(77 reference statements)
0
0
0
Order By: Relevance
“…For instance, to be a critical thinker about history one needs the skills of a historian; to practise reflective scepticism in mathematics one needs to have at least a basic understanding of mathematics (McPeck, 2015). Indeed, Nielsen et al (2022) found that students' prior knowledge may influence their likelihood of engaging in CT. In their study on whether first-year psychology students would develop CT around statistics-related content of their course, students who perceived that they had solid mathematical background were more likely to display higher levels of CT at the end of the two-semester-course study (Nielsen et al, 2022).…”
Section: Perceptions Towards Students' Level Of Critical Thinking Skillsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, to be a critical thinker about history one needs the skills of a historian; to practise reflective scepticism in mathematics one needs to have at least a basic understanding of mathematics (McPeck, 2015). Indeed, Nielsen et al (2022) found that students' prior knowledge may influence their likelihood of engaging in CT. In their study on whether first-year psychology students would develop CT around statistics-related content of their course, students who perceived that they had solid mathematical background were more likely to display higher levels of CT at the end of the two-semester-course study (Nielsen et al, 2022).…”
Section: Perceptions Towards Students' Level Of Critical Thinking Skillsmentioning
confidence: 99%
“…Indeed, Nielsen et al (2022) found that students' prior knowledge may influence their likelihood of engaging in CT. In their study on whether first-year psychology students would develop CT around statistics-related content of their course, students who perceived that they had solid mathematical background were more likely to display higher levels of CT at the end of the two-semester-course study (Nielsen et al, 2022). Moreover, students who believe that they would need to apply statistical knowledge in the future also exhibited higher performance in terms of statistics-related CT (Nielsen et al, 2022).…”
Section: Perceptions Towards Students' Level Of Critical Thinking Skillsmentioning
confidence: 99%
See 1 more Smart Citation